Die kontras tussen beboude omgewing en lewens- en wêrelds-beskouings - Steÿn, Das (Acta Structilia, 1995)
In architecture, contrast for much of the century has played an important role in the design of buildings (Brolin, 1980: 45). Even the SA Institute of Architects held a congress in contrast in 1991, but what is contrast? According to the Great Dictionary Van Dale, contrast means (1) "in the eye-catching contrast", and (2) "two different nature". The first sounds almost like what we experience in architecture, namely the physically perceptible differences in the built environment, and more specifically where the buildings are in real contradiction. The difference in "nature" refers to the human nature, usually its own personality, but human nature is more than just the innate, it also involves the cultural values of a people. These values are what give meaning to the individual’s existence. *This article is written in Afrikaans.